Critical analysis of the implications of new managerialism on ethical, democratic and professional values in public service - Vargas-Hernández, Jose G. (Redes, 2016)
This paper aims to critically analyze the implications of the new managerialism in the public service through ethical, democratic and professional values. It assumes the contradictions between the values that seek to promote the public service under the model of managerialism and the reality of its implementation. The method used is analytical-descriptive-normative from the critical perspective of the parallel developments of managerialism and public service. The theoretical and methodological framework that serves as a reference for this critical analysis is provided by the theories of organizational economics and public choice. The discussion concludes that there is a necessary conflict between ethical, democratic and professional values of these new organizational forms promoted by managerialism through the theories of economics and organizational public choice and traditional values of public service.